Wild populations of Pacific oysters (Magallana gigas) emerge during the blob heatwave in south Puget Sound, Washington USA - Beck, Emma Lee; Ruesink, Jennifer; Troyer, Stena; Behrens, Michael (Frontiers in Marine Science, 2024)
Marine heatwaves have altered ecosystems globally, including changing community composition and facilitating the spread of invasive species. In south Puget Sound, Washington (USA), non-native Pacific oysters (Magallana gigas) have been farmed extensively for almost a century and grown in enhancement sites, however, they have only recently recruited in the wild. This study explores how the appearance of Pacific oysters was related spatially (eight sites) and temporally (decade) to warmer summer water temperatures in south Puget Sound and compares oyster persistence across five sites where recruitment occurred. The largest recruitment event from 2012-2020 was in the summer of 2015, in the middle of the east Pacific Blob marine heatwave which led to warm water temperatures off the west coast of North America. Throughout the study period, the number of oyster recruits each year was positively correlated with warmer water temperatures. Oyster population densities differed across the five sites where recruitment occurred and generally declined after 2015, but showed no site by year interactions, which is consistent with spatially-variable recruitment and similar post-recruitment survival. Mean oyster shell heights also differed among sites, which could reflect different growth trajectories or recreational harvest patterns. This study supports the claim that warming sea surface temperatures may interact with species introductions to change modern biogeography.